2016
DOI: 10.17049/ahsbd.36978
|View full text |Cite
|
Sign up to set email alerts
|

Şi̇zofreni̇ Hastalarinin Ve Bakim Verenleri̇ni̇n Eği̇ti̇m Gereksi̇ni̇mleri̇ni̇n Beli̇rlenmesi̇

Abstract: ÖZET

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 11 publications
1
5
0
1
Order By: Relevance
“…Among similar studies conducted in Turkey, a study by Bademli et al to determine the educational needs of people with a diagnosis of schizophrenia and caregivers revealed that, as the education level of caregivers decreased, they had difficulties in coping with stress. 35 In this context, the study's results are similar to the literature. Caregivers in low socioeconomic levels have found that they prefer more helpless approach to cope with stress.…”
Section: Ta B L Esupporting
confidence: 86%
See 1 more Smart Citation
“…Among similar studies conducted in Turkey, a study by Bademli et al to determine the educational needs of people with a diagnosis of schizophrenia and caregivers revealed that, as the education level of caregivers decreased, they had difficulties in coping with stress. 35 In this context, the study's results are similar to the literature. Caregivers in low socioeconomic levels have found that they prefer more helpless approach to cope with stress.…”
Section: Ta B L Esupporting
confidence: 86%
“…Psychiatric nurses, who spend the most time with patients and caregivers within the healthcare team, are the most active members of the team working on this issue. Due to psychiatric nurses’ professional roles, they can contribute to reductions in caregivers’ care burden by providing counselling for caregivers after determining the difficulties they experience, such as their burdens and stress, and by providing psychoeducation in which training requirements are kept in priority . Determining the relationship between mental health problems and the emotional, social, physical, and financial burdens of caregivers for chronic mental disease patients helps protect and promote caregivers’ effective coping mechanisms for dealing with their burden and their patients’ mental health condition…”
Section: Introductionmentioning
confidence: 99%
“…All these may negatively affect patients’ continuity to CMHC. In the studies, lack of information and insight, drug side effects, inadequate family support, inadequate information about the disease and treatment, unhealthy coping methods have been reported to be the main causes of treatment noncompliance (Babacan Gümüş, 2006; Bademli et al, 2016; Compton, 2005; Dikeç & Kutlu, 2014; Doornbos, 2001; Kuşcu et al, 2007; Solomon, 2000; Ünal et al, 2006). In addition to disease symptoms and coping problems, fear of stigma affects the continuity as well.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were also obtained in the studies in the literature. In another study aimed at determining the educational needs of caregivers of patients with schizophrenia, it is stated that they need information about the early signs and symptoms of the illness, the effects of drugs, and coping with the patient's unusual and aggressive behaviors (Bademli et al, 2016;Raghavan et al, 2017). In the study conducted by Tamizi et al (2020), it was similarly reported that the family caregivers mentioned experiences such as lack of knowledge about the nature of the disorder, methods of treatment, how to provide care for the patient at home, insufficient awareness in managing the high-risk behavior of the patient and in dealing with the patient's resistance to treatment.…”
Section: Meaning Of Schizophreniamentioning
confidence: 99%